Nursing care for bed bath in patients with COVID-19: an integrative review - Cristina Tavares de Aguiar Avilar; Ítala Maria Araújo Andrade; Cawana da Silva do Nascimento; Larissa Vanessa Machado Viana; Thatiana Lameira Maciel Amaral; Patrícia Rezende do Prado (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify the main nursing care procedures for performing bed bath in patients with COVID-19. Method: an integrative literature review. Five stages were followed for this research: research question elaboration (identification of the problem), search of studies in literature, study assessment, data analysis, and presentation of review. To search for primary studies, the VHL and SciELO databases were selected. Results: initially, 55 publications were found. After reading and analyzing the abstracts, the sample consisted of 15 studies. Conclusion: patients with the new coronavirus have specific care to perform a bed bath, oral, intimate and skin hygiene. It is important that professionals use adequate personal protective equipment, perform humanized care, continuously observing patients' vital signs to avoid occurrence of adverse events, promoting patient safety.